THE RELATIONSHIP BETWEEN MENTAL HEALTH LITERACY AND STIGMA MENTAL DISORDERS IN THE SOKO VILLAGE COMMUNITY, BAGELEN DISTRICT, PURWOREJO REGENCY - Kartika Mahardika, Hyasinta Fernanda; Kustin, Kustin; Nuris Yuhbaba, Zidni (International Islamic Medicine Forum, 2021)
One of the significant health problems in the world, including in Indonesia, is mental health. Data from the Ministry of Health research conducted every five to six years regarding public health figures shows that the number of people with mental health problems in Indonesia needs serious treatment. The purpose of this study was to determine the relationship between Mental Health Literacy and Stigma Mental Disorders. This research is a correlation study using data collection techniques in the form of the Mental Health Knowledge Questionnaire (MHKQ) and the Peer Mental Illness Stigmatization Scale (PMISS). The research subjects were 52 using simple random sampling technique. Based on the results of the analysis showed that the correlation coefficient between mental health literacy and the stigma of mental disorders was 0.086 with a significance of 0. 542. The significance number in the results of this study exceeds the predetermined significance number, which is > 0.05. This means that there is no relationship between mental health literacy and the stigma of mental disorders. For further research, it is necessary to conduct further research on mental health literacy in the community in order to know the impact that can be caused on the stigma of mental disorders.